The Influence of Consumer Attractiveness and Accessibility on Decisions to Visit Tourism Yukita Rides Bengkulu - oktaviani, yeyen; Islamuddin; Faris Rashif Shiddiq Amru; Malisa Tri Wahyuni; Putri Mutia Sari (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2024)
A consumer's decision to visit is an integration process that combines knowledge to evaluate two or more alternative behaviors, and choose one among them. The aim of this research is to determine the influence of attractiveness and accessibility on the decision to visit Wahana Yukita Bengkulu Tourism. This research is a quantitative approach research with descriptive methods. Research location at Wahana Yukita Bengkulu Tourism in December 2023 until completion. The population in this research is all consumers who visit Wahana Yukita Bengkulu Tourism. This research used an incidental sampling technique with a total sample of 90 people. The data collection techniques in this research are interviews, observation, literature study, and questionnaires. The data analysis techniques used are multiple linear regression, coefficient of determination, and hypothesis testing. Based on the research results, it was found that the Fsig value = 0.000, this means that the Fsig value < α value, namely 0.005, so it can be concluded that the attractiveness (X1) and accessibility (X2) variables influence the visiting decision variable (Y) or together they have an influence. simultaneously